Correlation of Epistemic Curiosity and Cognitive Understanding Biology’s Student in Health and Pharmaceutical Biotechnology - Istiani, Fahrun; Bintari, Siti Harnina; Widiatningrum, Talitha (FMIPA UNNES, 2018)
Technology growing rapidly because technological development is required in all aspects of humanlife. Biotechnology is one of the branch of biology that is constantly evolving. Health andpharmaceutical biotechnology is one of the biotechnology which became the spotlight of the world.Biotechnology is part of science that commences from curiosity. One of curiosity type is epistemiccuriosity (EC). Epistemic curiosity contribute to give problem solving for the appearing issue. Thisneed higher order thinking. Higher order thinking need good cognitive understanding. The purpose ofthis study is to: 1) describe the epistemic curiosity (EC) Biology’ student to the development of healthand pharmaceutical biotechnology, 2) analyzing the correlation of epistemic curiosity (EC) andcognitive ability of biology’ student in health and pharmaceutical biotechnology. This researchincludes descriptive correlative with the research data is a cognitive understanding and EC ofbiology’ student. Cognitive understanding and EC data taken using a questionnaire (i-d scalecuriosity) and problem (the quiz). Average of EC scores is 26,1. A descriptive analysis of the averageEC is of 65.3% (high category). The average of student's cognitive understanding is 38.8%. (lowcategory). Quantitative correlation of cognitive understanding and EC was 0,208 (weak category).Qualitative correlation of cognitive understanding and EC was J category, that have a high EC butlow cognitive understanding.